2017
DOI: 10.1038/tp.2017.30
|View full text |Cite
|
Sign up to set email alerts
|

Erythrocyte glutathione levels as long-term predictor of transition to psychosis

Abstract: A high proportion of individuals deemed at elevated risk for psychosis will actually never progress to develop the illness. Pharmaceutical intervention may not be necessary in these cases, and may in fact be damaging depending on the invasiveness of the treatment strategy. This highlights the need for biomarkers that are better able to reliably differentiate between at-risk individuals who will subsequently transition to psychosis and those who will not. Low glutathione (GSH) levels have been observed in schiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 39 publications
0
17
0
Order By: Relevance
“…Models for prediction of transition to psychosis involved blood-based (20,56,71), electrophysiological (57,68,72), and neuroanatomical data using white and/or gray matter volume (38,44,51) or gyrification measures (55). Clinical models were trained on prodromal positive and negative symptoms, functioning, and family risk associated with functional decline; the neurocognitive modality was based on executive functions and verbal IQ (41) or speech features (54,73).…”
Section: Effect Of Data Modalitymentioning
confidence: 99%
“…Models for prediction of transition to psychosis involved blood-based (20,56,71), electrophysiological (57,68,72), and neuroanatomical data using white and/or gray matter volume (38,44,51) or gyrification measures (55). Clinical models were trained on prodromal positive and negative symptoms, functioning, and family risk associated with functional decline; the neurocognitive modality was based on executive functions and verbal IQ (41) or speech features (54,73).…”
Section: Effect Of Data Modalitymentioning
confidence: 99%
“…, 2002). GSH is the major cellular redox regulator and antioxidant, protecting cells from damage induced by reactive oxygen species (Lavoie et al. , 2017), and is a neurotransmitter/modulator that binds to the N-methyl-D-aspartate receptor (Chin et al., 2006) involved in anxiety, fear, learning and memory (Janáky et al.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, many studies rely upon more accessible blood and cerebral spinal fluid samples to characterize the molecular underpinnings of neuropsychiatric conditions [14-23]. Although there is variability between subjects, multiple studies have reported a significant reduction of GSH in SZ in peripherally accessible tissues and fluids, such as blood [6, 18, 19, 24-29]. …”
Section: Introductionmentioning
confidence: 99%